Neurological and Mental Health Responses to Pandemic Covid-19 - Mumtaz Ali Chhutto, Jawed Akhtar Samo, Inayatullah Awan, Mujeeb-Ul-Rehman, Muhammad Munwar Ali, Safdar Hussain Arain (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the neurological and mental health responses to pandemic Covid-19. Study design: Cohort study Place and duration of study: Department of Medicine, Chandka Medical College Hospital Larkana and Department of Medicine, Khairpur Medical College Hospital Khairpur Mir’s from 1st October 2021 to 31st March 2022. Methodology: Two hundred patients who suffered Covid-19 infection and 200 who had any other life event except Covid-19 were enrolled. All patients who were above 18 years of age and were positive for Covid-19 through reverse transcriptase PCR were included in the study.Global Psych trauma Screening was done by enlisting twenty-two items which assessed trauma related symptoms while five items only assessed the factors increasing risks. Results: There were 112 (56%) females and 88 (44%) males in Covid-19 patients and 150 (75%) females and 50 (25%) males in non-Covid patients. The mean age of the Covid-19 patients was 49.65±15.5 year while of non Covid patients was 39.02±12.01 years. A significant increase in post-traumatic stress disorder (PTSD) cases probability was noted in the Covid-19 cases than non Covid-19 related events. Neurological responses showed that patients who had suffered from Covid 19 infections had a generalized weakness with hyposmia formation. Conclusion: Covid-19 is related with high level of depression, anxiety, hyposmia and other mental and neurological responses. Keywords: Neurological health, Mental health, Response, Covid-19